Resolving policy conflicts for rapid growth in the world economy - BALASSA, B. (PSL Quarterly Review, 2014)
The legacy of the oil crisis, which simultaneously had an inflationary and a deflationary impact on the world economy, is still here five years later. While in recent years the United States has maintained economic expansion with little regard to its balance-of-payments consequences, in other countries the desire to lower inflation rates and/or to reduce balance-of-payment deficits has retarded economic expansion. Differences in growth rates have contributed to balance-of-payments imbalances which have translated into exchange rate changes far exceeding changes in purchasing power relationships. Such disequilibria has resulted in conflicting interests and strategies among industrial countries. In this paper the author argues for the application of specific measures to reduce policy conflicts and contribute to the growth of the world economy while minimising inflationary repercussions. JEL: E31, F31, F43